Autonomous streetlight brightness and angle adjustment system for enhanced road safety and energy efficiency - Samsudin, Esham Shukery; Muhd Yusoff, Muhd Firdaus; Abdul Rahman, Nur Atiqah; Jumaat, Hadi (Universiti Teknologi MARA, Sarawak, 2025)
An increasing number of road traffic accidents (RTAs) and the limitations of traditional streetlight systems have prompted the development of more intelligent, adaptive lighting solutions. This paper introduces an autonomous streetlight system that adaptively modifies brightness and angle coverage in response to environmental conditions and the presence of vehicles. The system incorporates a Raspberry Pi Pico 2 W microcontroller, Light Dependent Resistor (LDR) sensors, piezoelectric sensors, and MG995 servo motors to enhance energy efficiency and improve road safety. It also utilises Internet of Things (IoT) platforms such as Adafruit IO to facilitate fault detection with a status indicator, and GPS-based location tracking which enables prompt restoration, resulting in a reduction of energy consumption compared to conventional systems. Real testing has demonstrated the system’s reliability, addressing the limitations of conventional street lighting and setting the stage for smarter urban infrastructure.